2021
DOI: 10.3389/fgene.2021.743560
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Autophagy-Related Marker for Improved Differential Diagnosis of Rheumatoid Arthritis and Osteoarthritis

Abstract: Rheumatoid arthritis (RA) and osteoarthritis (OA) are two most common rheumatic diseases in the world. Although there are standard methods for the diagnosis of both RA and OA, the differentials in some cases are poor. With deepening research, the role of autophagy in maintaining cell homeostasis and thus enabling cells adapt to external environments has become increasingly prominent. Both RA and OA, two diseases with inherent differences in pathogenesis, gradually show differences in autophagy levels. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The knee and hip are two commonly affected joints, and approximately 30% of people over 45 years old show radiographic evidence of knee OA [ 2 ]. Characterized by cartilage degeneration and synovial inflammation, OA is often associated with the destruction of extracellular matrix (ECM) and reduced autophagy [ [3] , [4] , [5] ]. Therefore, expounding the mechanism that could affect the degradation of ECM, inflammatory response, and autophagy may provide a new direction for studying OA pathogenesis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The knee and hip are two commonly affected joints, and approximately 30% of people over 45 years old show radiographic evidence of knee OA [ 2 ]. Characterized by cartilage degeneration and synovial inflammation, OA is often associated with the destruction of extracellular matrix (ECM) and reduced autophagy [ [3] , [4] , [5] ]. Therefore, expounding the mechanism that could affect the degradation of ECM, inflammatory response, and autophagy may provide a new direction for studying OA pathogenesis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al. showed that autophagy and immune regulation played different roles in OA and RA, but both are significantly correlated ( 17 ). However, few reports have comprehensively investigated the relationship between ARG expression and cartilage immune infiltration in OA and the role of ARGs’ biological functions in cartilage immune infiltration.…”
Section: Introductionmentioning
confidence: 99%